Сведения «Худуд ал-алам» о болгарах и степень их достоверности - Бубенок, О.Б. (Хазарский альманах, 2017)
В хазарский период различные групы болгар Восточной и Юго-Восточной Европы были описаны в сочинениях мусульманских географов. Однако вхождение болгар в состав различных государственных образований раннего средневековья, а также их рассеяность на территории Европы породили довольно противоречивую и запутанную информацю о них в письменных источниках. Именно это и заставляет с особой осторожностью относиться к подобным сведениям и даже ставить под сомнение их достоверность. В особенной степени сказанное можно отнести к тексту «Худуд ал-‘Алам», ставящему перед исследователями массу вопросов. Usually, researchers see in “Hudud al-‘Alam” a difficult compiling written source of the ending of 10-th century AD, that does not deserve the special trust herein. However the evidences of anonymous treatise about the Bulgarians is of a special interest. So, “Hudud al-‘Alam” contains the information about the “Inner Bulgarians”. The analysis of text of this book allowed to come to the conclusion, that the anonymous author named the “Inner” those Bulgarians who lived in the steppes of Don basin and Azov Sea coast. Word-combination “Inner Bulgarians” could relate to the left (western) wing of the primary union of the nomadic Pro-Bulgarians. Besides, the anonymous author named the Volga Bulgarians as the “B.rtas”. He called also the Danube Bulgarians as “V.n.n.d.r’. Thus, the anonymous author of “Hudud al-‘Alam” used the different muslem written sources and as a result he met many difficulties. Therefore he created his the Map of the World. Besides, author of “Hudud al-‘Alam” reflected the new realities of the end of 10-th centuries AD. Therefore we must very carefully behave to the information of this medieval written source.